Practical analysis and reconstruction of shooting incidents - Hueske, Edward E. (CRC series in practical aspects of criminal and forensic investigations., 2016)
The book reviews basic firearm design and function, ammunition components, and terminology, explaining what constitutes pertinent evidence and appropriate results relative to autopsies, forensic laboratory analysis, and reenactments.